Development and validation of self-administration medication error tool - Natarajan, Anusha; Kumar, Bhargavi; Rajendran, Priyadarsini (International Journal of Research in Medical Sciences, 2025)
Background: Medication errors during self-administration pose significant risks to patient safety. The absence of standardized tools to assess and mitigate self-administration errors necessitates the development of a reliable instrument, to identify patients at risk and enhance patient outcomes by reducing adverse drug events. Methods: This quantitative study was conducted at Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), Pondicherry, between May 2023 and April 2024. The SAME tool was developed through a literature review, resulting in ten items assessing various aspects of medication self-administration. Content validity was assessed by four experts using a 4-point Likert scale. The Content Validity Index (CVI) was calculated, and the tool was tested on 100 subjects selected by convenience sampling. Internal consistency was measured using Cronbach’s alpha, and validity was assessed through Pearson Product Moment Correlation analysis. Results: The SAME tool included ten items covering confidence in medication administration, understanding instructions, and psychological impact of medication regimens. Validation: All items achieved a CVI of ≥0.88 indicating strong content validity. Cronbach’s alpha was 0.815, reflecting good internal consistency. Pearson correlation coefficients for individual items ranged from 0.492 to 0.740, all statistically significant (p<0.05), confirming the tool’s validity. The estimated prevalence of self-administration errors among participants was 17%, highlighting significant challenges in managing complex medication regimens. Conclusions: The SAME tool is a valid, reliable instrument for assessing self-administration medication errors in a clinical setting. It can identify patients at risk of medication errors, enabling targeted interventions to improve patient safety and outcomes.